Molecular dynamics simulation and analysis of pre-crystallization layer between liquid and solid states - Pavel V. Chirkov; Vladimir V. Dremov; Roman M. Kichigin; Alexey V. Karavaev; Filipp A. Sapozhnikov; Elena B. Cherepetskaya; Vladimir S. Dub; Ivan A. Ivanov; Sergey V. Salikhov (Scientific Reports)
Abstract Microscopic mechanisms of the crystallization from the melt provide for conversion of short-range order of a liquid state into the long-range order of a solid crystalline state and determine in much the primary microstructure. The ”choice” of proper crystalline structure is not a trivial process that is ruled by thermodynamics. On the other hand from the microscopic point of view it takes time for atoms to be incorporated into ordered structure that leads to formation of some intermediate region between disordered liquid and crystal. In the paper the origin and properties of the region that was called ”the pre–crystallization layer” are investigated within atomistic simulation approach by the classical molecular dynamics. The simulations were carried out for model Fe–Ni–Cr alloy that is crystallized into face centered cubic lattice. It was shown that the properties of the pre–crystallization layer are different from those of liquid and solid. Its structural peculiarities lead to formation of primary defects of just solidified material crystal structure and depend on the orientation of solidification front relative to the crystal lattice.